Christian Witness in a Multi-religious World Trajectories in the International Ecumenical Discussion - Anders, Christoph 1960-; Biehl, Michael 1956- (2019)
This article presents an overview of discussions on the ecumenical document 'Christian witness in a multi-religious world'. Beginning in Germany, it highlights the attention the document received and tracks some of the arguments through the changing contexts of the last decade connected to the document's invitation for a mission in respect of others. The challenge to implement the recommendations the document offers in a common endeavour to witness to Christ is then emphasized. The reception process for the document is described as an invitation to adopt and contextualize the principles and recommendations in one's own practising of mission and evangelism instead of sending comments on the text for revision.
Keywords: Ecumenical co-operation; ecumenical reception process; Mission; Respect; Witness